AWARENESS ON NOOTROPIC HERBS AMONG DENTAL STUDENTS HERBAL NOOTROPIC AGENTS - Raj, Denesh; Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2025)
Nootropics herb constitutes of compounds that enhance cognitive performance by increasing mental functions memory, creativity, motivation, and attention eventually causing individuals to be much alert and focused. These nootropic herbs tend to enhance the brain performances. To assess the awareness on nootropic herbs among dental students. A cross sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness on pharmacological properties, traditional uses, medicinal uses and memory enhancing function of the nootropic herbs from ayurvedic pharmacopoeia. The responses were recorded and analysed. 17% were aware of nootropic herbs.5% were aware of their pharmacological properties.3% were aware about traditional uses. 3 % aware about medicinal uses. 12%were aware of memory enhancing function. The awareness of nootropic herbs usage in clinical practice among dental students was found to be low in this study. Our findings emphasize the importance of incorporating several educational and training programs to dental students to sensitize them to look for alternative and herbal medicines in the treatment of diseases.